Sovietisation and the Estonian National Museum during 1940s-1950s - Karin Konksi (Journal of Ethnology and Folkloristics)
The article deals with the impacts of the policy of the 1940s-1950s Soviet authority on the Estonian National Museum. The first, introductory part observes the general frameworks of the (ethnographical) museums in the Soviet Union, thus providing an overview of the goal of Sovietisation policy – what was the system’s perception of the institution that the ENM was supposed to become. The main part of the article focuses on Sovietisation practice in the ENM: what kind of reorganisation took place within the work of the museum in connection with political changes, whether and how the new norms were adapted to and to what extent they were adopted. The source material used for the treatment of the subject matter comprises, in addition to the ENM’s archive materials, the memories of three ethnologists who worked in the ENM during the observed period.